The hero of the Saskatchewan : life among the Ojibway and Cree Indians in Canada. - MacLean, John, 1851-1928. (Barrie, Ont. : The Barrie Examiner Printing and Publishing House, 1891)
Printed two columns to the page. Mode of access: Internet.